Leveraging Digital Finance Literacy to Enhance Financial Inclusion for Migrant Communities in Malaysia - Risman, Asep; Syarif, Andam Dewi (CV. Era Digital Nusantara, 2025)
This Community Service Activity is intended to improve the financial inclusion of Indonesian migrant workers in Malaysia, focusing on those residing on Penang Island. As an integral part of the Indonesian diaspora, migrant workers often face challenges in accessing financial services, which in turn can affect their overall welfare. Enhancing financial inclusion is considered a strategic approach to supporting their economic well-being and long-term sustainability. The activity was carried out through educational interventions designed to strengthen digital finance literacy. The method involved a combination of lectures and practical training. The materials delivered included an overview of digital finance, types of digital finance services, their benefits, and step-by-step guidance on using digital financel applications—such as e-wallets and digital gold platforms. Practical components covered processes such as account registration, fund deposits and withdrawals, as well as transactions (purchasing and selling) within digital marketplaces in collaboration with financial technology providers. To evaluate the effectiveness of the program, a questionnaire was administered to participants. The results indicated that 73.3% of participants expressed a high level of satisfaction, while 57.3% perceived the program as important and beneficial. Tangible outputs from this activity include educational videos published on YouTube, articles featured in mass media, peer-reviewed journal publications, and registered Intellectual Property Rights (IPR).